REGENERON PHARMACEUTICALS, INC v KYMAB LTD (No. 2). Issue 8 (6th December 2018) - ,
Abstract: Patents – European patents – Pharmaceuticals – Antibody production – Genetic engineering – Transgenic mice – Infringement – Validity – Appeal to Court of Appeal – Decision below overturned – Terms of injunctive relief – Whether to extend to non-infringing eukaryotic cells – Scope of disclosure to be ordered – Costs on appeal and below – Successful argument not advanced below – Apportionment as between co-defendants – Interim costs order – Stay pending further appeal – Whether to impose conditions